2013
DOI: 10.1029/2012jd018629
|View full text |Cite
|
Sign up to set email alerts
|

Direct radiative effects of sea salt for the Mediterranean region under conditions of low to moderate wind speeds

Abstract: [1] This study deals with the direct radiative effect of sea salt on the regional scale, within both the shortwave and longwave ranges. The COSMO-ART model system has been extended and applied for a large part of Europe and adjacent waters within this investigation. For the radiation calculations, we determined the sea salt optical properties based on Mie calculations, giving the optical properties for the three sea salt modes and eight spectral intervals. The simulated sea salt aerosol optical depth is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 81 publications
3
39
0
Order By: Relevance
“…Figure 15a and b) indicates that PMA period is characterised by moderate TOA DRE (mean of −8 ± 3 W m −2 ) and BOA DRE (mean of −11 ± 4 W m −2 ). Such estimates at Ersa station are found to be consistent with direct SW effects of sea salt documented by Lundgren et al (2013), who used the COSMO-ART model over the Mediterranean Basin and reported a SW DRE from −5 to −10 W m −2 at the surface and an AOD between 0.1 and 0.2 (at 550 nm).…”
Section: Pma Physical Properties In Comparison With Dust and Bbp Periodssupporting
confidence: 72%
“…Figure 15a and b) indicates that PMA period is characterised by moderate TOA DRE (mean of −8 ± 3 W m −2 ) and BOA DRE (mean of −11 ± 4 W m −2 ). Such estimates at Ersa station are found to be consistent with direct SW effects of sea salt documented by Lundgren et al (2013), who used the COSMO-ART model over the Mediterranean Basin and reported a SW DRE from −5 to −10 W m −2 at the surface and an AOD between 0.1 and 0.2 (at 550 nm).…”
Section: Pma Physical Properties In Comparison With Dust and Bbp Periodssupporting
confidence: 72%
“…The type of areas examined regarding wood burning impacts on air quality may range from a specific residential area or a suburb (Hellen et al, 2008 andYli-Tuomi et al, 2015) to a large city such as London (Fuller et al, 2014;Young et al, 2015) and to a regional level, such as Flanders, Belgium (Maenhaut et al, 2012). They all agree on a substantial contribution of RWB to PM mass, even when the use is for secondary heating.…”
Section: Introductionmentioning
confidence: 93%
“…The fluxes and composition of the smallest particles are especially uncertain. In addition to direct radiative effects (Lundgren et al, 2012), sea-salt aerosols may feedback on meteorology by acting as CCNs, their activity being dependent on the organic fraction contributed by phytoplankton (Ovadnevaite et al, 2011). In addition, phytoplankton is a source of dimethyl sulfide (DMS) and a minor source of isoprene (Guenther et al, 1995;Gantt et al, 2010;Meskhidze et al, 2011).…”
Section: Emissionsmentioning
confidence: 99%